Analisis Strategi 5c Dalam Penyelesaian Kredit Bermasalah Bank Perkreditan Rakyat Md Di Lamongan Jawa Timur - Kusuma Wijaya (JEMAP, 2019)
This study aims to find out the 5Cs strategy adopted in the  process of settlement of non-performing loans. Research data  were analyzed with descriptive qualitative approach, and collected by studying documents, observation and interviews. These results indicated that the strategy had been implemented effectively in resolving loan problem showed by the decrease of loan problem number from year 2012 to 2014. Data obtained from the Peoples Credit Bank (PCB) MD in the provision of credit could not be separated from non-performing loans. The factors are the failure of the debtor's business, bad characters, house transfering and death of the borrower. Credit settlement strategy undertaken by PCB MD were rescheduling, reconditioning and restructuring. Rescheduling was a change in credit terms concerning the payment schedule and time period, the amount of installment, and the grace period. Reconditioning (back requirements) was a partial or total changes in credit terms which was not limited to, changes in payment schedules, duration, and or other requirements, as long as no change plafon credit. And restructuring (or realignment) was including changes in conditions before credit terms: the addition of bank funds, conversion of all or part of the areas of interest into a new loan principal.